2017
DOI: 10.1016/j.ebiom.2017.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent T-cell Dynamics and Cytokine Cascade Following rVSV-ZEBOV Immunization

Abstract: BackgroundThe recent West African Ebola epidemic led to accelerated efforts to test Ebola vaccine candidates. As part of the World Health Organisation-led VSV Ebola Consortium (VEBCON), we performed a phase I clinical trial investigating rVSV-ZEBOV (a recombinant vesicular stomatitis virus-vectored Ebola vaccine), which has recently demonstrated protection from Ebola virus disease (EVD) in phase III clinical trials and is currently in advanced stages of licensing. So far, correlates of immune protection are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 33 publications
6
54
1
Order By: Relevance
“…28 Studies are in progress to elucidate immune mechanisms of protection, including the roles of antibody-dependent cellular cytotoxicity, innate immunity, and T cells. 29,30 Data from this study support several important conclusions. First, we confirm the previously described pattern of early onset, mild to moderate, well tolerated, transient, and dose-dependent local and systemic adverse events induced by rVSVΔG-ZEBOV-GP.…”
Section: Discussionsupporting
confidence: 80%
“…28 Studies are in progress to elucidate immune mechanisms of protection, including the roles of antibody-dependent cellular cytotoxicity, innate immunity, and T cells. 29,30 Data from this study support several important conclusions. First, we confirm the previously described pattern of early onset, mild to moderate, well tolerated, transient, and dose-dependent local and systemic adverse events induced by rVSVΔG-ZEBOV-GP.…”
Section: Discussionsupporting
confidence: 80%
“…Here, EBOV GP specific T-cells secreted mainly CD107a and TNFα, while lower dose groups showed antigen-specific T-cell responses. 70 Recent advances in our understanding of the innate immune system and the use of systems biology approaches are beginning to reveal the fundamental mechanisms by which the innate immune system orchestrates protective immune responses to vaccination. We investigated innate immune responses following VSV-EBOV immunization and our data revealed an innate immune signature that correlated with antibody responses in the Hamburg VSV-EBOV vaccine trial.…”
Section: Correlates Of Protection and Duration Of Immune Responsesmentioning
confidence: 99%
“…All participants were injected with vaccine doses ranging from 3 × 10 5 to 5 × 10 7 PFU or placebo (NCT02283099, NCT02296983). 34 , 35 The results from these three trials demonstrated good antibody responses in all vaccinees and neutralizing antibodies were elicited by day 28 in 107 out of 126 vaccinees (85%). 36 , 37 However, during one trial in Geneva, 11 out of 51 (22%) participants without any previous history of joint disease had an onset of arthralgia in the second week after vaccination.…”
Section: Introductionmentioning
confidence: 94%
“…39 In-depth analysis of samples from one trial corroborated this finding of increased IP-10 levels after vaccination and found a general activation of T cells with a significant induction of Th1 cytokines in response to vaccination. 35 A different study found a correlation between the antibody response to vaccination and an increase in the circulation of a specific subset of CD4+ T cells, cTfh17 cells. 40 …”
Section: Introductionmentioning
confidence: 99%